The Place of The System of Images In the Plot and Composition of “Baburnoma” (International Journal of Scientific Trends, 2025)
In this article, the description of the world of images in the work “Boburnoma”, the role of images in the structure of the work, as well as historical images, in particular the role of the image of Kasimbek in the plot and composition of the work, are subject to analysis.